2023
DOI: 10.1111/jsr.13895
|View full text |Cite
|
Sign up to set email alerts
|

Light therapy in insomnia disorder: A systematic review and meta‐analysis

Abstract: SummaryIn the management of insomnia, physicians and patients are seeking alternative therapeutics to sleeping pills, in addition to sleep hygiene and cognitive behavioural therapy. Bright light therapy (LT) has proven its efficacy in circadian and mood disorders. We conducted a systematic literature review and meta‐analysis according to Cochrane and PRISMA guidelines and using the databases Medline, Cochrane, and Web of Science, with a special focus on light therapy and insomnia. Twenty‐two studies with a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…A meta-analysis on light therapy for insomnia showed small positive effects on sleep (Van Maanen et al, 2016) and this is an area worthy of further investigation, especially because a circadian sleep-wake rhythm disorder is frequently comorbid with insomnia. Chambe et al (2023) came to similar conclusions: light therapy may have some promise, but further RCTs are necessary.…”
Section: Exercise Light Therapy Music and Noninvasive Brain Stimulationmentioning
confidence: 75%
“…A meta-analysis on light therapy for insomnia showed small positive effects on sleep (Van Maanen et al, 2016) and this is an area worthy of further investigation, especially because a circadian sleep-wake rhythm disorder is frequently comorbid with insomnia. Chambe et al (2023) came to similar conclusions: light therapy may have some promise, but further RCTs are necessary.…”
Section: Exercise Light Therapy Music and Noninvasive Brain Stimulationmentioning
confidence: 75%
“…LT is natural, simple, relatively inexpensive, and useful as an adjuvant treatment for sleep disorders due to its few interactions with other treatment options. A systematic review and meta-analysis, which involved 22 studies and 685 participants, demonstrated the significant improvement of wake after sleep onset with LT in managing insomnia, supporting the overall effectiveness of LT in treating sleep problems [ 21 ], as highlighted by another meta-analysis of 53 studies involving 1154 participants [ 19 ]. However, only a few studies have examined the effects of LT on sleep-related parameters.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is necessary to prevent disharmony in the circadian rhythm and maintain a balanced state by providing light with the appropriate timing, intensity, duration, and wavelength, similar to natural light; however, modern city lifestyles make this difficult. There are many studies that investigate the utility of sources of artificial lighting in the management of sleep problems [ 19 , 20 , 21 ]. Pharmacological agents, cognitive behavioral therapy, and psychosocial interventions have been traditionally used to treat sleep problems, but light therapy (LT) is receiving more attention due to the limitations that accompany the traditional therapies, such as drug side effects, cost, and limitations of time and space [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To execute this task, a recently published SR titled ‘Light Therapy in Insomnia Disorder: A Systematic Review and Meta-Analysis’ was selected, and the databases were queried using the keywords stipulated in the original paper. 5 Two key rationales underpinned the selection of this review: first, it yielded a relatively moderate number of studies, and second, its eligibility criteria were somewhat subjective, and challenging to discern during the screening process, making it a suitable testbed to evaluate GPT-3.5’s capabilities. For instance, this study enrolled patients experiencing sleep difficulties but did not specify the particular types of sleep disorders although reviewers did not face much trouble but models had difficulties with studies that included patients with secondary sleeping troubles like patients with cancer.…”
mentioning
confidence: 99%
“…These numpy arrays, along with the numpy arrays generated by the researchers, were employed to compute sensitivity, specificity, accuracy and the F1 score for both the researchers and the prompts. The labels used as the ‘gold standard’ were the studies included in the selected SR. 5 …”
mentioning
confidence: 99%